Nitro-benzylideneoxymorphone, a bifunctional mu and delta opioid receptor ligand with high mu opioid receptor efficacy - Olson, Keith M.; Devereaux, Andrea L.; Chatterjee, Payal; Saldaña-Shumaker, Savanah L.; Shafer, Amanda; Plotkin, Adam; Kandasamy, Ram; MacKerell, Alexander D.; Traynor, John R.; Cunningham, Christopher W. (Frontiers in Pharmacology, 2023)
There is a major societal need for analgesics with less tolerance, dependence, and abuse liability. Preclinical rodent studies suggest that bifunctional ligands with both mu (MOPr) and delta (DOPr) opioid receptor activity may produce analgesia with reduced tolerance and other side effects. This study explores the structure-activity relationships (SAR) of our previously reported MOPr/DOPr lead, benzylideneoxymorphone (BOM) with C7-methylene-substituted analogs. One compound, nitro-BOM (NBOM, 12) emerged as a potent MOPr agonist and DOPr partial agonist in vitro that produced antinociceptive effects in the warm water tail withdrawal assay in C57Bl/6 mice. Molecular modeling experiments using the Site Identification by Ligand Competitive Saturation (SILCS) method support the hypothesis that the increased MOPr efficacy of NBOM is due to the substituted benzylidene ring occupying a nonpolar region within the MOPr agonist state. Though antinociceptive tolerance and non-specific toxicity was observed on repeated administration, NBOM provides an important new tool for understanding MOPr/DOPr pharmacology.